JUDUL : PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN RETURN ON ASSET (ROA) TERHADAP PERUBAHAN HARGA SAHAM YANG GO PUBLIC DI BURSA EFEK INDONESIA - B21108049, Iin Mutmainnah (Jurnal Pembangunan dan Pemerataan, 2012)
Banking has an important role in business especially related to the fund availability as investment and working capital. The good financial performance of banks will be responded by capital market in the form of increasing stock price. This research aims to know whether the banks performance that represented by capital (Capital Adequacy Ratio) and profitability (Return on Asset) simultaneously and partially influence banks stock return. The sample was taken by using purposive judgement sampling method so that the researcher gets three years research period which covers ten banks that are listed and their stocks are actively traded in Indonesian Stock Exchange (IDX). Analysis result shows that Capital Adequacy Ratio (CAR) and Return On Asset (ROA) simultaneously and partially influence stock return. Regressions coefficient shows that the influence of ROA is bigger than the influence of CAR. The relationship between independent variables (CAR and ROA) with dependent variable (banks stock return) is very strong. Simultaneously, those two variables can explain 68,3% the change in stock return, while the rests are explained by other variable which are not observed. Keywords: Capital Adequacy Ratio (CAR), Return On Asset (ROA) and Stock Return